Some Properties of Connectedness in Grill Topological Spaces - Suliman, Saad S.; R.B. , Esmaeel (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
We use the idea of Grill, this study generalized a new sort of linked space like –connected –hyperconnected and investigated its features, as well as the relationship between it and previously described notation. It also developed new sorts of functions, such as hyperconnected space, and identifying their relationship, by offering numerous instance and attributes that belong to this set. This set will serve as a starting point for further research into the sets many future possibilities. Also, we use some of the theorems and observations previously studied and relate them to the grill and the Alpha group, and benefit from them in order to obtain new results in this research. We applied the concept of Connected to them and obtained results related to Connected. The sources related to the Connected and Alpha were considered as starting points and an important basis in this research.